2009
DOI: 10.1590/s1519-69842009000500012
|View full text |Cite
|
Sign up to set email alerts
|

Primate community of the tropical rain forests of Saracá-Taqüera National Forest, Pará, Brazil

Abstract: Brazil is the richest country in the world in terms of primate species and the Amazonian rain forest is one of the richest biomes containing 15 (ca. 90%) of the Neotropical primate genera. Although considered key elements in conservation strategies, there is only anecdotal information on primates for several protected areas within the region. Here we present new data on the community composition of the primates in the Saracá-Taqüera National Forest (429,600 ha), an actively mined, bauxite rich area, in Pará, B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
4
0
1
Order By: Relevance
“…In particular, C. olivaceus sightings were greatly reduced in areas where they co‐existed with S. apella ; Lehman's explanation was scramble competition rather than intergroup competition between the two species. Oliveira et al's [] survey of Saracá‐Taqüera National Forest, Pará, Brazil, found S. apella to be the most abundant primate, and they never directly observed C. olivaceus , despite reports of it living in the area and C. olivaceus museum specimens from there. Surveys in northern French Guiana showed that in 15 of 16 sites where both capuchin species were present, S. apella was more abundant than C. olivaceus .…”
Section: Ecological Differences For Cebus and Sapajus In Sympatrymentioning
confidence: 99%
“…In particular, C. olivaceus sightings were greatly reduced in areas where they co‐existed with S. apella ; Lehman's explanation was scramble competition rather than intergroup competition between the two species. Oliveira et al's [] survey of Saracá‐Taqüera National Forest, Pará, Brazil, found S. apella to be the most abundant primate, and they never directly observed C. olivaceus , despite reports of it living in the area and C. olivaceus museum specimens from there. Surveys in northern French Guiana showed that in 15 of 16 sites where both capuchin species were present, S. apella was more abundant than C. olivaceus .…”
Section: Ecological Differences For Cebus and Sapajus In Sympatrymentioning
confidence: 99%
“…Type of record: VO = visual observation, V = vocalization, T = track, F = feces, B = burrow, C = carcass, CT = camera trap, LT = live trap, PT = pitfall trap, I = interview. Global (IUCN 2016), National (MMA 2014) and Regional (Pará 2006) only by interviews and published records (Oliveira et al 2009). The wedge-capped capuchin, C. olivaceus, has been recorded from the left margin of the Trombetas River (Oliveira et al 2009), although the STNF is located on the right margin.…”
Section: Discussionmentioning
confidence: 99%
“…Global (IUCN 2016), National (MMA 2014) and Regional (Pará 2006) only by interviews and published records (Oliveira et al 2009). The wedge-capped capuchin, C. olivaceus, has been recorded from the left margin of the Trombetas River (Oliveira et al 2009), although the STNF is located on the right margin. In the Amazon, rivers typically act as geographic barriers to primates (Peres et al 1996;Boubli et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Dessa forma, a espécie ocorre nas florestas de várzea e em manchas de floresta inseridas em matriz de savana nos municípios de Santana, Macapá, Mazagão, Itaubal, Cutias, Ferreira Gomes e Porto Grande. O registro da espécie no município de Oriximiná, no Pará, é provavelmente um equívoco, pois a espécie que ocorre naquela região é A. macconnelli (Oliveira et al, 2009), que é amplamente distribuída ao longo da margem norte do rio Amazonas. É preciso uma maior amostragem no interflúvio Iriri-Xingu, pois não se sabe ao certo qual espécie de Alouatta ocorre nessa região.…”
Section: Distribuiçãounclassified

Ficha de Alouatta belzebul

Mônica Mafra Valença-Montenegro,
Francisco Virgínio de Souza,
Ítalo Mourthé
et al. 2024
Datasets - Sistema SALVE - ICMBio